The Importance of Oral Literature from the Perspective of Ethnology - Amrullah Nabil; Ahmad Wali Bismel (Randwick International of Education and Linguistics Science Journal, 2023)
Literature is a cultural part of society which is included of education, believes, arts, morals, laws, disciplines, traditions, habits and capacity in the society. Oral literature is the oldest type of literature which has a great role in formation of classical literature. Literary genre in a geographical limitation helps to know the culture and tradition of its people. It would happen if we have deep insight of ethnology from perspective of oral literature. Ethnology helps to know social habits of the people through its myths, proverbs, articles, couplets, stories etc. as a result, we can say that oral literature has an important role in ethnology and without deep insight in oral literature and literary genres of literature knowing people would be not possible.